ANALISIS KESEIMBANGAN LINI PROSES PCB ASSEMBLY RADIO P155 SRS DI PT PANASONIC MANUFACTURING INDONESIA - Citra Amelia Pratiwi; Arief Nurdini; Ardhy Lazuardy (Jurnal Teknik dan Science, 2024)
PT Panasonic Manufacturing Indonesia is one of the largest manufacturing companies producing electronic products in Indonesia, achieving significant growth and development in its production processes. Ensuring an efficient production process requires maintaining proper line balancing to achieve smooth operations. However, the radio P155 Srs production line experienced workload imbalances that led to bottlenecks and time losses. These issues arose due to factors such as insufficiently skilled workers and mismatched workloads that were not aligned with operators' abilities. Such conditions can lead to worker fatigue and reduced motivation and negatively impact work effectiveness. Research conducted using the Ranked Position Weight (RPW) method demonstrated improvements by reducing the number of workstations from 12 to 8. This optimization resulted in increased track efficiency, which improved from 65.10% and 57.43% to 83.10% and 85.94%.